A rare cause of ischemic heart failure in a neonate - Zainab AlAwadhi; Deepu Abraham; Nilesh Oswal; Mohamed Kasem (Wolters Kluwer Medknow Publications, 2022)
Herein, we present a case of ischemic heart failure that occurred immediately after birth in a neonate due to coronary artery fistula (CAF) from the left main coronary artery to the left atrial appendage associated with high pulmonary artery pressure. Ischemic heart failure in a neonate with a structurally normal heart is rare. Furthermore, CAF resulting in ischemic heart failure is very rare in neonates. We believe that the small CAF caused symptoms during the first few days of life due to moderate pulmonary hypertension which resulted in a low cardiac output. The coronary perfusion improved after the normalization of the pulmonary blood pressure and improvement of the cardiac output. Echocardiography is helpful when a CAF is suspected and can be confirmed using a cardiac computed tomography scan. Small CAFs are unlikely to cause symptoms in infants, provided there are no other factors affecting the cardiac output status.